Perlindungan Hukum Terhadap Bank Pada Fasilitas Kredit Debitur Penanam Modal Asing - Hendera Hendera (Postgraduate of Jayabaya University, 2017)
Credit Channel to Foreign Investment Company has a high risk if incase non-performing loan happen. Due on those cases, the author borders some several issues: 1) What’s issues that causing non-performing loan in credit channel by the foreign investment company? 2) How the bank’s risk if non-performing loan occurs in credit channel by the foreign investment company? 3) How is law providing a legal protection against bank in case non-performing loan occurs in credit channel by the foreign investment company?. Research methods for this journal is using an empiric theory with sosio-legal research. The results are credit channel to a foreign investment company is not having particular rules of legal protection yet against banking industry if non-performing loan happens. So, the government is expected to make a constitution of legal protection against bank for credit channel to foreign investment company so bank is assuring a strong legal certainty.